The mythological image of Korkyt Ata: Spiritual Mentor and Hero in Kazakh and Turkic Culture (Journal of Oriental Studies, 2024)
In the analysis of the mythological role of Korkyt Ata in Kazakh culture and other ethnic contexts, complex symbolism and universal aspects emerge. Korkyt Ata, a legendary figure, possesses numerous mythological nuances related to heroism, fate, and spiritual wisdom. Comparative studies reveal that the image of Korkyt Ata has varying shades in Kazakh, Turkish, and Azerbaijani mythology. He appears as both a warrior hero and a spiritual mentor. His legends often incorporate symbols of water, connected with birth and death, as well as motifs of celestial and Tengri-related associations. These elements combine cosmic and earthly aspects, reflecting deep cultural and philosophical notions of life, death, and immortality. The image of Korkyt Ata, being archetypal, transcends cultural and epochal boundaries, inspiring contemplation of profound life questions and universal mythological themes. Keywords: Korkyt Ata, Mythological Symbolism, Cross-Cultural Interpretation, Heroic Archetype, Spiritual Mentor, Cultural Context